2017
DOI: 10.1063/1.4994793
|View full text |Cite
|
Sign up to set email alerts
|

Electron cyclotron emission at the fundamental harmonic in GDT magnetic mirror

Abstract: New electron cyclotron emission (ECE) diagnostics has been installed to facilitate the successful experiment on electron cyclotron plasma heating (ECRH) experiment at the large open magnetic trap GDT in Budker Institute. The particularities of ECE in the vicinity of the ECRH frequency were studied experimentally for a broad range of discharge scenarios. Measured thermal emission has partly validated the existing physical conceptions about the microwave plasma heating in the machine. Besides expected emission o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
4
8
0
Order By: Relevance
“…In addition, new ECE diagnostics will provide data on the lineintegrated electron pressure in discharge with a high resolution in time. The similar idea was used previously to confirm our understanding of X1 ECRH at GDT with the ECE operating in the vicinity of the ECRH frequency 54.5 GHz [7,8]. Besides, measured by this diagnostics non-thermal ECE have unambiguously confirmed the existence of suprathermal electrons in GDT with energies about 10 keV.…”
Section: Second Harmonic Ece Of Bulk and Hot Electronssupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, new ECE diagnostics will provide data on the lineintegrated electron pressure in discharge with a high resolution in time. The similar idea was used previously to confirm our understanding of X1 ECRH at GDT with the ECE operating in the vicinity of the ECRH frequency 54.5 GHz [7,8]. Besides, measured by this diagnostics non-thermal ECE have unambiguously confirmed the existence of suprathermal electrons in GDT with energies about 10 keV.…”
Section: Second Harmonic Ece Of Bulk and Hot Electronssupporting
confidence: 76%
“…First difficulty is related to the very complicate plasma dielectric response near the first cyclotron harmonic that results in strong refraction [6]. Although this feature is used in the present ECRH scheme and direct ECE measurements validate our understanding of the involved physics [7,8], next-step devices would probably require simpler solutions. Other weakness of the X1 scheme is related to the accessibility condition ω > ω pe for microwaves.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the new ECE diagnostics operates near the heating frequency in the geometry reversed to the ECRH one. Measured thermal emission for different discharge scenarios has essentially validated the existing physical conceptions about the microwave heating in the machine [16]. Somewhat against our expectations, it has been found that ECRH may start from weakly absorbing plasma, but during the discharge the evolution of the electron temperature leads to an eventual transition to optically thick plasma; before we believed that ECRH always starts with optically thick plasma.…”
supporting
confidence: 68%
“…Nevertheless, suprathermal electrons play an essential role in ECR plasma start-up recently implemented at GDT: electrons with energies about 10 keV are entirely responsible for the gas ionization and plasma pressure at initial stages of gas breakdown and seed plasma build-up [21]. Measured non-thermal ECE have unambiguously confirmed the existence of suprathermal electrons generated during the ECR heating of the main plasma [16]. Explanation of time dependence of ECE level observed in the varying magnetic field and decaying plasma is a rather challenging task.…”
mentioning
confidence: 99%
“…According to the new data, the energy and lifetime of fast electrons are determined and the classical regime of their confinement is confirmed for the main phase of the plasma discharge. With the previous ECE system at the fundamental EC harmonic, these measurements were difficult since the emission of fast electrons was effectively screened by the bulk plasma [8].…”
mentioning
confidence: 99%